Effect of Sugarcane Bagasse Content and Modification on the Properties of Sugarcane Bagasse/Poly(lactic Acid) Biocomposites - Youxue Peng; Wen Lei; Wangwang Yu; Yong Chen (Molecules)
In this study, poly(lactic acid) biocomposites were prepared from sugarcane bagasse (SB) via extrusion and injection molding. The effects of the content and inorganic salt modification of SB on the properties of the biocomposites were investigated. The results showed that the incorporation of SB reduced the biocomposites’ mechanical strength and modulus as well as thermal stability but increased their crystallinity, hydrophobicity, and water absorption compared with neat PLA. Among all the biocomposites, the sample containing 30 wt % SB(SB-30/PLA) had the best comprehensive performances, with tensile strength, tensile modulus, flexural strength, and crystallinity values of 31.78 MPa, 219.49 MPa, 53.25 MPa, and 16.8%, respectively. After SB modification with Na2SO4 and MgSO4, the increased interfacial adhesion led to a considerable improvement in reinforcement and increases in the flexural strength, flexural modulus, impact strength, and crystallinity of SB-30/PLA; furthermore, the biocomposite became more thermally stable and hydrophobic and contained much less water. In conclusion, SB-30/PLA, especially after MgSO4 modification, is an ideal degradable biocomposite for applications in packaging, decoration, and other areas.